Defensive Silence, Defensive Voice, Knowledge Hiding, and Counterproductive Work Behavior Through the Lens of Stimulus-Organism-Response - Qi, Fang-Shu; Ramayah, T. (Frontiers in Psychology, 2022)
Rising negative emotions are like “time bombs” that impede productivity in the workplace. The present investigation provides an insight into the effects of defensive silence and defensive voice on counterproductive work behavior through knowledge hiding in the context of knowledge workers in Chinese academic institutions. Partial square least structural equation modeling (PLS-SEM) was applied to the current samples. The study obtained conjecture the proposed mediating role of knowledge hiding between the negative working attitude and counterproductive work behavior, which is against the organizational norms and performance. The result indicates that the positive relationships exist from defensive silence and defensive voice to counterproductive work behavior, mediated by knowledge hiding. This study links knowledge hiding literature and stimulus-organism-response (SOR) to better explore the academic behavior in a knowledge setting.